2010
DOI: 10.1387/ijdb.082797tg
|View full text |Cite
|
Sign up to set email alerts
|

On the role of placental Major Histocompatibility Complex and decidual leukocytes in implantation and pregnancy success using non-human primate models

Abstract: While there is broad agreement that interactions of the human maternal immune system with the tissues and cells of the implanting embryo are likely to be critical contributors to pregnancy success, there remains a dearth of information which directly confirms this expectation. Although animal models of reproductive function often provide opportunities for confirming such hypotheses, progress in this area has been sporadic due to limitations of traditional laboratory or agricultural animal models, such as roden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 94 publications
(110 reference statements)
1
24
1
Order By: Relevance
“…Thus, if primate models are necessary, members of Old World monkeys such as rhesus macaques or baboons may represent appropriate alternatives. It has been proven for placental circulation, gas exchange, endocrinology and immunological as well as to model in parts aspects of pregnancy hypertension or other defects [253][254][255][256][257][258][259]. However, their shallow trophoblast invasion limited the usability as model species for preeclampsia [71].…”
Section: Euarchontogliresmentioning
confidence: 99%
“…Thus, if primate models are necessary, members of Old World monkeys such as rhesus macaques or baboons may represent appropriate alternatives. It has been proven for placental circulation, gas exchange, endocrinology and immunological as well as to model in parts aspects of pregnancy hypertension or other defects [253][254][255][256][257][258][259]. However, their shallow trophoblast invasion limited the usability as model species for preeclampsia [71].…”
Section: Euarchontogliresmentioning
confidence: 99%
“…We have previously shown that CSF3 (G-CSF) is important in the functional differentiation of peripheral blood monocytes to macrophages in vitro [24], and in the decidual environment, perhaps CSF2 may serve a similar role. This suggests that dNK cells (and perhaps T cells and resident macrophages themselves) are important in the maturation of additional decidual macrophages, which increase dramatically during the first weeks of gestation [25][26][27]. In addition to these growth and differentiation factors, the potent chemokine CCL2 (previously known as MCP-1) was strongly increased in the decidua compared to pNK cells.…”
Section: Cytokines and Growth Factorsmentioning
confidence: 99%
“…Complex immune reactions mediating the maternal tolerance of the trophoblast may contribute extra MHC-dependent selective steps in mammals, including primates [74]. Placental expression of foetal MHC class I molecules has been detected in several primate species [75]. These molecules, partially encoded by the paternal haplotype, may represent 'non-self' for the mother but nevertheless contribute to the regulation of the maternal immune response throughout gestation [76].…”
Section: Choosing For Diversity or For Particular Genes (Hypotheses 2mentioning
confidence: 99%